Women’s Agency and Institutional Change in Small-Scale Fisheries: Evidence from Talisayan, Indonesia (International Forum of Researchers and Lecturers, 2025)
Women play crucial yet often invisible roles in small-scale fisheries, particularly in post-harvest processing, marketing, and household financial management. Despite their contributions, women remain marginalized in fisheries governance and institutional decision-making. This paper examines how women in Talisayan, Berau Regency, East Kalimantan, Indonesia move from the margins to the center of fisheries governance by mobilizing everyday practices and collective enterprises to drive institutional change. The study adopts a qualitative case study approach, drawing on in-depth interviews, focus group discussions, participant observation, and document analysis involving 35 informants, including women fish processors, leaders of Kelompok Usaha Bersama (KUB), and village officials. Data were analyzed thematically using Parsons’ AGIL framework, Berger and Luckmann’s social constructivism, and social capital theory. Findings highlight four dynamics. First, women adapt to economic and ecological pressures by diversifying livelihoods and creating informal saving schemes. Second, they achieve collective goals through KUB, enhancing bargaining power, leadership opportunities, and market access. Third, women foster social integration by building solidarity, trust, and institutional legitimacy within their communities. Finally, through cultural reproduction and innovation, they transform gender norms and gain recognition as institutional actors, embedding inclusivity into local fisheries governance. This study contributes to debates on gender and development by demonstrating how women’s agency in small-scale fisheries generates both livelihood resilience and institutional transformation. It argues that empowering women through collective enterprises is essential for achieving equitable and sustainable fisheries governance in Indonesia and beyond.